Dysregulation of lncRNAs in Rheumatoid Arthritis: Biomarkers, Pathogenesis and Potential Therapeutic Targets - Miao, Chenggui; Bai, Liangliang; Yang, Yaru; Huang, Jinling (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is a chronic autoimmune disease of unknown etiology, mainly manifested by persistent abnormal proliferation of fibroblast-like synoviocytes (FLSs), inflammation, synovial hyperplasia and cartilage erosion, accompanied by joint swelling and joint destruction. Abnormal expression or function of long noncoding RNAs (lncRNAs) are closely related to human diseases, including cancers, mental diseases, autoimmune diseases and others. The abnormal sequence and spatial structure of lncRNAs, the disorder expression and the abnormal interaction with the binding protein will lead to the change of gene expression in the way of epigenetic modification. Increasing evidence demonstrated that lncRNAs were involved in the activation of FLSs, which played a key role in the pathogenesis of RA. In this review, the research progress of lncRNAs in the pathogenesis of RA was systematically summarized, including the role of lncRNAs in the diagnosis of RA, the regulatory mechanism of lncRNAs in the pathogenesis of RA, and the intervention role of lncRNAs in the treatment of RA. Furthermore, the activated signal pathways, the role of DNA methylation and other mechanism have also been overview in this review.